Applications of Dermatoglyphics in Dentistry: A Narrative Review - Ankita Gupta; Bhavna Singh; Manoj Vishwakarma (Journal of Orofacial Research, 2023)
The word ’dermatoglyphics’ comes from two Greek words (derma, skin and glyphe, carve) and refers to the study of the epidermal skin ridge formations which appear on the fingers, palms of the hands and soles of the feet. There are numerous applications of dermatoglyphics in dentistry as lot of studies done on dental caries and dermatoglyphics show that there is a strong correlation of dermatoglyphic patterns to the prevalence of dental caries. Dermatoglyphics should be adopted by more dental professionals and researchers for oral cavity related studies, leading to new discoveries for an early diagnosis, prompt treatment and more effective prevention of many genetic disorders of the oral cavity and other diseases whose etiology may be influenced directly or indirectly by genetic inheritance. In the future, it may serve as an important tool that can predict the future health of a person.